2007
DOI: 10.1124/dmd.107.017566
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Metabolic Profile of Free, Conjugated, and Total Silymarin Flavonolignans in Human Plasma after Oral Administration of Milk Thistle Extract

Abstract: ABSTRACT:Silymarin, a mixture of polyphenolic flavonoids extracted from milk thistle (Silybum marianum), is composed mainly of silychristin, silydianin, silybin A, silybin B (SB B ), isosilybin A (ISB A ), and isosilybin B. In this study, the plasma concentrations of free (unconjugated), conjugated (sulfated and glucuronidated), and total (free and conjugated) silymarin flavonolignans were measured using liquid chromatography-electrospray ionization-mass spectrometry, after a single oral dose of 600 mg of stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
157
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 25 publications
10
157
0
Order By: Relevance
“…Silymarin (Silybum marianum), the polyphenolic fraction from Milk Thistle is used for hepatoprotection in humans (Flora et al 1998, Jacobs et al 2002, Fraschini et al 2002, Ladas and Kelly, 2003, Wen et al 2007) and demonstrated good protection in various toxic paradigms of experimental liver diseases in small laboratory animals (Radko and Cybulski 2007). Silymarin functions as an antioxidant, which absorbs and regulates the intracellular glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin (Silybum marianum), the polyphenolic fraction from Milk Thistle is used for hepatoprotection in humans (Flora et al 1998, Jacobs et al 2002, Fraschini et al 2002, Ladas and Kelly, 2003, Wen et al 2007) and demonstrated good protection in various toxic paradigms of experimental liver diseases in small laboratory animals (Radko and Cybulski 2007). Silymarin functions as an antioxidant, which absorbs and regulates the intracellular glutathione.…”
Section: Introductionmentioning
confidence: 99%
“…As with other flavolignans, limitations of silybin use include low water solubility, low bioavailability, and poor intestinal absorption [14]. Derivatives of silybin with improved solubility may surmount these pharmacologic limitations [15,16].…”
mentioning
confidence: 99%
“…As reported by Rickling et al (1995) or Wen et al (2008), silymarin flavonolignans after oral administration were quickly metabolized to their conjugates, primarily forming glucuronides, and the conjugates were primary components present in human plasma. Wen et al (2008) further demonstrated that all six silymarin flavonolignans were rapidly eliminated, and the conjugated silymarin flavonolignans had relatively longer half-lives than their free forms.…”
Section: Discussionmentioning
confidence: 86%
“…Wen et al (2008) further demonstrated that all six silymarin flavonolignans were rapidly eliminated, and the conjugated silymarin flavonolignans had relatively longer half-lives than their free forms. In our study, plasma conjugated Silymarin complex digestibility (%) SB was determined at all sampling times in period B with the highest plasma concentration at the last sampling time (13:00 h), it was approximately 6 h after feeding.…”
Section: Discussionmentioning
confidence: 93%